The properties of agricultural waste particle composite reinforced with woven cotton fabric / Mohd Iqbal Misnon ... [et al.] - Misnon, Mohd Iqbal; Bahari, Shahril Anuar; Ahmad, Mohd Rozi; Wan Ahmad, Wan Yunus; Salleh, Jamil; Ab Kadir, Muhammad Ismail (Research Management Institute (RMI), 2010)
The production ofparticle composites using agricultural waste materials is an area ofsignificant research interest. 1ngeneral the properties ofagricultural waste particle composites are considered to be inferior to those ofcommercial particleboards. In this study, the inclusion of woven colton fabric has been used to overcome this drawback. Particle composites were manufactures from coconut shell- and rubberwood-particles using urea formaldehyde as a binder andcombined with woven cotton fabric to reinforce the material. Thefabricated agricultural waste particle composites were then evaluated with respect to the effect ofthe number offabric layers in the composite structure and the inherent effect on the mechanical (flexural and impact strength) and physical (water absorption and thickness swelling) properties. Agricultural waste particle composites without any reinforcement were used as control samples in this study. The test results indicate that theflexural andimpactproperties ofparticle composites reinforced with woven colton fabric are better than those for the control samples. It was also determined that both the mechanical andphysical properties improve with increasing fabric layers, except with respect to thickness swelling.